A New Trick of Old Dogs: Can Kappa Opioid Receptor Antagonist Properties of Antidepressants Assist in Treating Treatment-Resistant Depression (TRD)? - Shaul Schreiber; Lee Keidan; Chaim G. Pick (Pharmaceuticals)
Background/Objectives: Approximately one in five individuals will experience major depressive disorder (MDD), and 30% exhibit resistance to standard antidepressant treatments, resulting in a diagnosis of treatment-resistant depression (TRD). Historically, opium was used effectively to treat depression; however, when other medications were introduced, its use was discontinued due to addiction and other hazards. Recently, kappa opioid receptor (KOR) antagonism has been proposed as a potential mechanism for treating TRD. The main research question is whether commonly used psychotropic medications possess KOR antagonist properties and whether this characteristic could contribute to their efficacy in TRD. Methods: We investigated the antinociceptive effects of many psychotropic medications and their interactions with the opioid system. Mice were tested with a hotplate or tail-flick after being injected with different doses of these agents. Results: The antidepressants mianserin and mirtazapine (separately) induced dose-dependent antinociception, each yielding a biphasic dose–response curve. Similarly, the antidepressant venlafaxine produced a potent effect and reboxetine produced a weak effect. The antipsychotics risperidone and amisulpride exhibited a dose-dependent antinociceptive effect. The sedative–hypnotic zolpidem induced a weak bi-phasic dose-dependent antinociceptive effect. All seven psychotropic medications elicited antinociception, which was reversed by the non-selective opiate antagonist naloxone and, separately, by the kappa-selective antagonist Nor-BNI. Conclusions: Clinical studies are mandatory to establish the potential efficacy of augmentation of the treatment with antidepressants with these drugs in persons with treatment-resistant depression and the optimal dosage of medications prescribed. We suggest a possible beneficial effect of antidepressants with kappa antagonistic properties.